Language Learning Strategies And Student Thinking Style: A Case Study of Marginal Children at Relawan Anak Sumatera Selatan (RASS) - Diana Fridayanti; Jaya Nur Iman; Dita Rizki Anggraini (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research explores the relationship between language learning strategies and the thinking styles of marginalized children under the care of the Relawan Anak Sumatera Selatan (RASS) community. The research aims to identify how these students, who face various socio-economic challenges, adopt specific language learning strategies and how their unique thinking styles influence these choices. Through qualitative methods using field Observations and in-depth interviews. Findings show that marginalized students often use social and memory strategies due to resource constraints and external support, and their thinking styles, This research contributes to the broader discourse on inclusive education by highlighting the importance of adaptive teaching methods that address the diverse cognitive and socio-economic backgrounds of students.